Mental Health Psychoeducation for Female Prisoners: Promoting Justice and Better Treatment (Study of Women’s Correctional Institution Class IIA Semarang) - Wahanisa, Rofi; Prihastuty, Rahmawati; Nuzulia, Siti; Pratiwi, Pradipta Christy; Rahmawati, Dyah Ayu; Al Fikry, Ahmad Habib; Rohmawati, Santi; Cahyani F, Ardia Pramesthi Regita; Al Jazuli, Qasim (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement), 2023)
This study examines the implementation of mental health psychoeducation for female prisoners in Class IIA Semarang Women’s Correctional Institution, focusing on the promotion of justice and improved treatment. Mental health challenges are prevalent among incarcerated individuals, stemming from factors like monotony, anxiety, stress, and depression associated with confinement. Through a series of psychoeducational sessions covering self-awareness, interpersonal communication, psychological first aid, emotion regulation, stress management, and positive self-talk, the research investigates the effectiveness of these interventions in enhancing mental health and well-being among female inmates. Post-test results reveal promising outcomes, with 57.69% of participants exhibiting a very healthy mental health status, 38.46% classified as mentally healthy, and 3.85% falling into the moderate mental health category. These findings underscore the significance of psychoeducational interventions in promoting justice and better treatment within the prison system.